(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2013)
Gastrocnemius is the muscle of choice for reconstruction of defects involving soft tissue loss over the upper third tibia as well as knee joint. We present a series of 12 patients who underwent gastrocnemius muscle flap(Medial head, proximally based) coverage for this type of defects. Patients age-18 years or above. There were 9 males and 3 females. In all cases, delayed reconstruction was performed ranging from 1 week to 3 months after the creation of defects. Maximum number of pts were within 18-35 years age groups (66.66%), 75% were victims of RTA, 75% had associated fractures. Results of surgery were graded as excellent(83.33%) to good(16.67%) depending upon the outcome and functional restoration of patients. There was no case of complete muscle flap failure. Minor complications were ( 1 pt. developed partial flap necrosis & 1 pt. developed infection) noted but none required a separate operative procedure. We have found this procedure to be reliable, technically easy, biologically sound and esthetically acceptable. JCMCTA 2012 ; 23 (2): 58-61